Carboniferous tetrapod fauna of the fossil lycopsid trees at Joggins and the origin of the hollow tree guild - John H. Calder; Andrew C. Scott; Brian L. Hebert; Andrew C. Milner; Matthew R. Stimson (Proceedings of the Geologists' Association, 2026)

What a load of rubbish: The impact of anthropogenic litter on urban freshwater diversity - Victoria S. Milner; Matthew J. Hill; Kieran J. Gething; Summer B. Cunningham (Environmental Pollution, 2025)

Long‐term changes in macroinvertebrate communities across high‐latitude streams - Alexander M. Milner; Eva M. Loza Vega; Thomas J. Matthews; Sarah C. Conn; Fredric M. Windsor (Global Change Biology, 2023)
Long‐term records of benthic macroinvertebrates in high‐latitude streams are essential for understanding climatic changes, including extreme events (e.g. floods). Data extending over multiple decades are typically scarce. Here, we investigated macroinvertebrate community structural change (including alpha and beta diversity and gain and loss of species) over 22 years (1994–2016) in 10 stream systems across Denali National Park (Alaska, USA) in relation to climatological and meteorological drivers (e.g. air temperature, snowpack depth, precipitation). We hypothesised that increases in air temperature and reduced snowpack depth, due to climatic change, would reduce beta and gamma diversity but increase alpha diversity. Findings showed temporal trends in alpha diversity were variable across streams, with oscillating patterns in many snowmelt‐ and rainfall runoff‐fed streams linked to climatic variation (temperature and precipitation), but increased over time in several streams supported by a mixture of water sources, including more stable groundwater‐fed streams. Beta‐diversity over the time series was highly variable, yet marked transitions were observed in response to extreme snowpack accumulation (1999–2000), where species loss drove turnover. Gamma diversity did not significantly increase or decrease over time. Investigating trends in individual taxa, several taxa were lost and gained during a relative constrained time period (2000–2006), likely in response to climatic variability and significant shifts in instream environmental conditions. Findings demonstrate the importance of long‐term biological studies in stream ecosystems and highlight the vulnerability of high‐latitude streams to climate change.

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Wheat root systems as a breeding target for climate resilience - Eric S. Ober; Samir Alahmad; James Cockram; Cristian Forestan; Lee T. Hickey; Josefine Kant; Marco Maccaferri; Emily Marr; Matthew Milner; Francisco Pinto; Charlotte Rambla; Matthew Reynolds; et al. (Theoretical and Applied Genetics, 2021)
In the coming decades, larger genetic gains in yield will be necessary to meet projected demand, and this must be achieved despite the destabilizing impacts of climate change on crop production. The root systems of crops capture the water and nutrients needed to support crop growth, and improved root systems tailored to the challenges of specific agricultural environments could improve climate resiliency. Each component of root initiation, growth and development is controlled genetically and responds to the environment, which translates to a complex quantitative system to navigate for the breeder, but also a world of opportunity given the right tools. In this review, we argue that it is important to know more about the ‘hidden half’ of crop plants and hypothesize that crop improvement could be further enhanced using approaches that directly target selection for root system architecture. To explore these issues, we focus predominantly on bread wheat ( Triticum aestivum L.), a staple crop that plays a major role in underpinning global food security. We review the tools available for root phenotyping under controlled and field conditions and the use of these platforms alongside modern genetics and genomics resources to dissect the genetic architecture controlling the wheat root system. To contextualize these advances for applied wheat breeding, we explore questions surrounding which root system architectures should be selected for, which agricultural environments and genetic trait configurations of breeding populations are these best suited to, and how might direct selection for these root ideotypes be implemented in practice.

Evidence for centennial‐scale Lateglacial and early Holocene climatic complexity from Quoyloo Meadow, Orkney, Scotland - Rhys G. O. Timms; Ashley M. Abrook; Ian P. Matthews; Christopher P. Francis; Agnieszka Mroczkowska; Ian Candy; Stephen J. Brooks; Alice M. Milner; Adrian P. Palmer (Journal of Quaternary Science, 2021)
The influence of the North Atlantic on the margins of Europe means the region is particularly sensitive to changes in the ocean–atmospheric system. During the Last Glacial–Interglacial Transition (16–8 cal ka bp ) this system was repeatedly disrupted, leading to a series of abrupt and short‐lived shifts in climate. Despite much research, the number and magnitude of these ‘centennial‐scale’ events is not well understood. To address this, we expand upon investigations at Quoyloo Meadow, Orkney, Scotland, one of the best chronologically constrained palaeoclimate records in northern Britain. By coupling stable isotope and chironomid fossil analyses with existing data, this study identifies multiple phases of centennial‐scale disturbance at: c . 14.0, 11.1, 10.8, 10.5, 10.45 and 10.3 cal ka bp , with the events at 14.0 and 10.3 exhibiting a particularly pronounced cold‐climate signature. During the Holocene, the strongest response to climate forcing was at c . 10.3–10.0 cal ka bp , expressed as a two‐stage drop in mean July temperatures, a shift in pollen spectra indicative of ‘less‐stable’ climatic regimes, and a depletion in δ 18 O values. We interpret this as the first reliably dated incidence of the ‘10.3‐ka event’ in the British Isles and consider the wider impact of this climatic reversal in other Holocene records.

Extreme drought pushes stream invertebrate communities over functional thresholds - Thomas W. H. Aspin; Kieran Khamis; Thomas J. Matthews; Alexander M. Milner; Matthew J. O’Callaghan; Mark Trimmer; Guy Woodward; Mark E. Ledger (Global Change Biology, 2019)
Functional traits are increasingly being used to predict extinction risks and range shifts under long‐term climate change scenarios, but have rarely been used to study vulnerability to extreme climatic events, such as supraseasonal droughts. In streams, drought intensification can cross thresholds of habitat loss, where marginal changes in environmental conditions trigger disproportionate biotic responses. However, these thresholds have been studied only from a structural perspective, and the existence of functional nonlinearity remains unknown. We explored trends in invertebrate community functional traits along a gradient of drought intensity, simulated over 18 months, using mesocosms analogous to lowland headwater streams. We modelled the responses of 16 traits based on a priori predictions of trait filtering by drought, and also examined the responses of trait profile groups (TPGs) identified via hierarchical cluster analysis. As responses to drought intensification were both linear and nonlinear, generalized additive models (GAMs) were chosen to model response curves, with the slopes of fitted splines used to detect functional thresholds during drought. Drought triggered significant responses in 12 (75%) of the a priori‐selected traits. Behavioural traits describing movement (dispersal, locomotion) and diet were sensitive to moderate‐intensity drought, as channels fragmented into isolated pools. By comparison, morphological and physiological traits showed little response until surface water was lost, at which point we observed sudden shifts in body size, respiration mode and thermal tolerance. Responses varied widely among TPGs, ranging from population collapses of non‐aerial dispersers as channels fragmented to irruptions of small, eurythermic dietary generalists upon extreme dewatering. Our study demonstrates for the first time that relatively small changes in drought intensity can trigger disproportionately large functional shifts in stream communities, suggesting that traits‐based approaches could be particularly useful for diagnosing catastrophic ecological responses to global change.

Myogenic potential of mesenchymal stem cells isolated from porcine adipose tissue - Derek J. Milner; Massimo Bionaz; Elisa Monaco; Jo Ann Cameron; Matthew B. Wheeler (Cell and Tissue Research, 2018)

The Why, What, and How of Global Biodiversity Indicators Beyond the 2010 Target - JULIA P. G. JONES; BEN COLLEN; GILES ATKINSON; PETER W. J. BAXTER; PHILIP BUBB; JANINE B. ILLIAN; TODD E. KATZNER; AIDAN KEANE; JONATHAN LOH; EVE MCDONALD‐MADDEN; EMILY NICHOLSON; HENRIQUE M. PEREIRA; et al. (Conservation Biology, 2011)
The 2010 biodiversity target agreed by signatories to the Convention on Biological Diversity directed the attention of conservation professionals toward the development of indicators with which to measure changes in biological diversity at the global scale. We considered why global biodiversity indicators are needed, what characteristics successful global indicators have, and how existing indicators perform. Because monitoring could absorb a large proportion of funds available for conservation, we believe indicators should be linked explicitly to monitoring objectives and decisions about which monitoring schemes deserve funding should be informed by predictions of the value of such schemes to decision making. We suggest that raising awareness among the public and policy makers, auditing management actions, and informing policy choices are the most important global monitoring objectives. Using four well‐developed indicators of biological diversity (extent of forests, coverage of protected areas, Living Planet Index, Red List Index) as examples, we analyzed the characteristics needed for indicators to meet these objectives. We recommend that conservation professionals improve on existing indicators by eliminating spatial biases in data availability, fill gaps in information about ecosystems other than forests, and improve understanding of the way indicators respond to policy changes. Monitoring is not an end in itself, and we believe it is vital that the ultimate objectives of global monitoring of biological diversity inform development of new indicators.

Impact of a Community‐Based Payment for Environmental Services Intervention on Forest Use in Menabe, Madagascar - MATTHEW SOMMERVILLE; E.J. MILNER‐GULLAND; MICHAEL RAHAJAHARISON; JULIA P.G. JONES (Conservation Biology, 2010)
Despite the growing interest in conservation approaches that include payments for environmental services (PES), few evaluations of the influence of such interventions on behaviors of individuals have been conducted . We used self‐reported changes in six legal and illegal forest‐use behaviors to investigate the way in which a PES for biodiversity conservation intervention in Menabe, Madagascar, influenced behavior . Individuals ( n = 864) from eight intervention communities and five control communities answered questions on their forest‐use behaviors before and after the intervention began, as well as on their reasons for changing and their attitudes to various institutions . The payments had little impact on individuals’ reported decisions to change behaviors, but it had a strong impact on individuals’ attitudes . Payments appeared to legitimize monitoring of behaviors by the implementing nongovernmental organization (NGO), but did not act as a behavioral driver in their own right . Although there were no clear differences between changes in behaviors in the intervention and control communities, the intervention did influence motivations for change . Fear of local forest associations and the implementing NGO were strong motivators for changing behavior in communities with the PES intervention, whereas fear of the national government was the main reason given for change in control communities . Behavioral changes were most stable where fear of local organizations motivated the change . Our results highlight the interactions between different incentives people face when making behavioral decisions and the importance of considering the full range of incentives when designing community‐based PES interventions .